Southeast Asia Against Human Trafficking by the Sea: Comparison between Indonesia and The Philippines - Santoso, Inggrid Rosemary; Silviani, Ninne Zahara; Febriyani, Emiliya (Hang Tuah Law Journal, 2025)
This study compares efforts to prevent human trafficking (TPPO) via maritime routes between Indonesia and the Philippines. TPPO is a transnational crime involving sexual exploitation, forced labor, and online fraud. This study employs a normative juridical approach, examining the implementation of the United Nations Convention against Transnational Organized Crime (UNTOC) and the ASEAN Plan of Action in both countries. This study is based on a qualitative literature study, utilizing secondary data from both primary and secondary legal sources. The findings indicate that Indonesia has implemented Law No. 21 of 2007 on the Eradication of Human Trafficking, while the Philippines uses the Anti-Trafficking in Persons Act of 2003 and Expanded Anti-Trafficking in Persons Act of 2012. Both nations have strengthened maritime patrols and inter-agency coordination, but the effectiveness of law enforcement still faces challenges, such as limited resources and insufficient training. Another issue is the need for enhanced cross-border cooperation. This study recommends strengthening regional collaboration, raising public awareness, and improving victim protection measures. These findings aim to contribute to better TPPO policies in Southeast Asia, especially in Indonesia and the Philippines.